STRES DAN KECEMASAN PADA DOSEN YANG MELAKSANAKAN KULIAH DARING PADA MASA PANDEMI COVID-19 - Sugesti Aliftitah; Nelyta Oktavianisya (Sekolah Tinggi Ilmu Kesehatan Kepanjen, 2021)
Online learning applied since March 2020, during 10 month passed, obstacle raised among students and lecturers which found during online learning, student had difficulties on phone signal especially students from island near Madura island, student poorly understood about the topic given by the lecturer. Problem faced by lecturer such as student didn’t pay attention during online learning, and some of lecturers clueless with online learning app. This will raise stress and anxiety for lecturers who was doing online learning. The aim of this study was to represent anxiety and stress level of lecturers during online learning for pandemic covid 19 period. The design of this study was descriptive design. The Population in this study were all of lecturers of Universitas Wiraraja as much as 168 lecturers with sample 63 lecturers. The result of this study showed that respondent mostly on medium level of anxiety were 33 people (52,4%) and the stress level of respondent mostly on medium level of stress werw 42 people (66,7 %). A lecturer expected to improve their coping mechanism in overcoming stress and anxiety during online learning for pandemic time. By proper stress management, it will increase lecturer work performances on this pandemic condition. Keywords: Anxiety, Stress, Covid 19, lecturers